Identification of complex III, NQR, and SDH as primary bioenergetic enzymes during the stationary phase of Pseudomonas aeruginosa cultured in urine-like conditions - Hu, Yuyao; Yuan, Ming; Julian, Alexander; Tuz, Karina; Juárez, Oscar (Frontiers in Microbiology, 2024)
Pseudomonas aeruginosa is a common cause of urinary tract infections by strains that are often multidrug resistant, representing a major challenge to the world's health care system. This microorganism has a highly adaptable metabolism that allows it to colonize many environments, including the urinary tract. In this work, we have characterized the metabolic strategies used by stationary phase P. aeruginosa cells cultivated in urine-like media to understand the adaptations used by this microorganism to survive and produce disease. Our proteomics results show that cells rely on the Entner-Duodoroff pathway, pentose phosphate pathway, the Krebs cycle/ glyoxylate shunt and the aerobic oxidative phosphorylation to survive in urine-like media and other conditions. A deep characterization of the oxidative phosphorylation showed that the respiratory rate of stationary phase cells is increased 3-4 times compared to cells in the logarithmic phase of growth, indicating that the aerobic metabolism plays critical roles in the stationary phase of cells grown in urine like media. Moreover, the data show that respiratory complex III, succinate dehydrogenase and the NADH dehydrogenase NQR have important functions and could be used as targets to develop new antibiotics against this bacterium.